Fifteen Marseilleviruses Newly Isolated From Three Water Samples in Japan Reveal Local Diversity of Marseilleviridae - Aoki, Keita; Hagiwara, Reika; Akashi, Motohiro; Sasaki, Kenta; Murata, Kazuyoshi; Ogata, Hiroyuki; Takemura, Masaharu (Frontiers in Microbiology, 2019)
The family Marseilleviridae, defined as a group of icosahedral double-stranded DNA viruses with particle size of approximately 250 nm and genome size of 350–380 kbp, belongs to the nucleo-cytoplasmic family of large DNA viruses. The family Marseilleviridae is currently classified into lineages A–E. In this study, we isolated 12 or 15 new members of the family Marseilleviridae from three sampling locations in Japan. Molecular phylogenetic analysis of the MCP genes showed that the new viruses could be further classified into three groups, hokutoviruses, kashiwazakiviruses, and kyotoviruses. Hokutoviruses were closely related to lineage B, kyotoviruses were related to lineage A, and kashiwazakiviruses were also classified into lineage B but a new putative subgroup of lineage B, revealing the diversity of this lineage. Interestingly, more than two viruses with slightly different MCP genes were isolated from a single water sample from a single location, i.e., two hokutoviruses and one kashiwazakivirus were isolated from a small reservoir, five kashiwazakiviruses from the mouth of a river, and five kyotoviruses from fresh water of a river, suggesting that several milliliters of water samples contain several types of giant viruses. Amoeba cells infected with hokutoviruses or kashiwazakiviruses exhibited a “bunch” formation consisting of normal and infected cells similarly to a tupanvirus, whereas cells infected with kyotoviruses or tokyovirus did not. These results suggest the previously unrecognized local diversity of the family Marseilleviridae in aquatic environments.